So, ça c’est ça: So and ça fait in Two Regions of Francophone Louisiana - Root, Jamie; Reaves, Alisha (Minorités linguistiques et société / Linguistic Minorities and Society, 2025)
Prior research on discourse marker use in Louisiana French suggests that discourse markers borrowed from English generally predominate in Francophone Louisiana. However, regional variation has largely been ignored. An analysis of interviews with 16 native speakers of Louisiana French in two regions of Louisiana found a statistically significant regional effect on the distribution of the discourse markers so and ça fait. These results demonstrate not only that the influence of English on the Louisiana French discourse marker system has been overstated, but also that treating French in Louisiana as a homogeneous variety can lead to misleading conclusions.